Century‐long apparent decrease in intrinsic water‐use efficiency with no evidence of progressive nutrient limitation in African tropical forests - Marijn Bauters; Sofie Meeus; Matti Barthel; Piet Stoffelen; Hannes P. T. De Deurwaerder; Félicien Meunier; Travis W. Drake; Quentin Ponette; Jerôme Ebuy; Pieter Vermeir; Hans Beeckman; Francis wyffels; et al. (Global Change Biology, 2020)
Forests exhibit leaf‐ and ecosystem‐level responses to environmental changes. Specifically, rising carbon dioxide (CO 2 ) levels over the past century are expected to have increased the intrinsic water‐use efficiency (iWUE) of tropical trees while the ecosystem is gradually pushed into progressive nutrient limitation. Due to the long‐term character of these changes, however, observational datasets to validate both paradigms are limited in space and time. In this study, we used a unique herbarium record to go back nearly a century and show that despite the rise in CO 2 concentrations, iWUE has decreased in central African tropical trees in the Congo Basin. Although we find evidence that points to leaf‐level adaptation to increasing CO 2 —that is, increasing photosynthesis‐related nutrients and decreasing maximum stomatal conductance, a decrease in leaf δ 13 C clearly indicates a decreasing iWUE over time. Additionally, the stoichiometric carbon to nitrogen and nitrogen to phosphorus ratios in the leaves show no sign of progressive nutrient limitation as they have remained constant since 1938, which suggests that nutrients have not increasingly limited productivity in this biome. Altogether, the data suggest that other environmental factors, such as increasing temperature, might have negatively affected net photosynthesis and consequently downregulated the iWUE. Results from this study reveal that the second largest tropical forest on Earth has responded differently to recent environmental changes than expected, highlighting the need for further on‐ground monitoring in the Congo Basin.